PENGARUH KONSENTRASI DAN INTERVAL WAKTU PEMBERIAN PUPUK ORGANIK CAIR (POC) NASA TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays saccharata Sturt) - M. Syufrin Pasaribu; Wan Arfiani Barus; Heri Kurnianto (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2011)
AbsrtactThe study aims to evaluate the growth response and production of sweet corn with the treatment concentration and time interval giving NASA POC at a different level. Group Randomized Factorial Design (RAK-F) with two factors were studied, namely: Liquid Organic Fertilizer Concentration Factors NASA (N) is divided into four standard No = No provision, N1 = 1.13 ml / 0.5 l of water / plot, N2 = 2.26 ml / 0.5 l of water / plot, N3 = 3.39 ml / 0.5 l of water / plot, Giving time and interval factors NASA POC (I) is divided into 3 time ie I1 = 1-week, I2 = 2 weeks and I3 = 3 weeks. While the parameters observed were plant height (cm), number of leaves (pieces), cob length (cm), production per plot (kg), and contains a number of seeds per cob (seeds). The results showed that the concentration of POC NASA administration significantly influenced the parameters plant height, cob length, yield per plot, and contains a number of seeds per cob, but not significant different in the parameters of the leaf. As for the interval timing of NASA POC is not a real effect on all parameters of the observations. For the interaction between concentration and interval timing of NASA POC significant effect only on the cob and different length parameter is not significant at the other observation parameters.Keywords: Zea mays saccharat Sturt, concentraion dan time interval